Radiographic evaluation of orthodontic treatment by means of four different cephalometric superimposition methods - Marcos Augusto Lenza; Adilson Alves de Carvalho; Eduardo Beaton Lenza; Mauricio Guilherme Lenza; Hianne Miranda de Torres; João Batista de Souza (Dental Press Editora, 2015)
INTRODUCTION: Despite discussion on the merit of various cephalometric superimposition methods, there remains a need to assess which one can be used in daily practice with reasonably accuracy and less working time. OBJECTIVE: The aim of this study was to investigate four methods of cephalometric superimposition by means of assessing the longitudinal changes in craniofacial morphology caused by growth and response of adolescents with Class I malocclusion to orthodontic treatment involving first premolar extraction. METHODS: Pretreatment (T1) and post-treatment (T2) standardized lateral cephalometric radiographs of 31 adolescents (20 females and 11 males), with Angle Class I malocclusion and indication of premolar extraction, participated in this study. Radiographs were digitized, traced and had structures identified by means of a cephalometric software. Four superimposition methods were used: Björk structural method, Steiner/Tweed SN line, Ricketts N-Ba line at N-point and Ricketts N-Ba line at CC-point. Positional changes were quantified by horizontal and vertical linear changes in the following cephalometric landmarks: anterior/posterior nasal spine (ANS and PNS), gnathion (Gn), Gonion (Go), Pogonion (Pog), A-point and B-point. Differences between T1 and T2 in horizontal and vertical positional changes for all superimposition methods were assessed by one-way analysis of variance (ANOVA) and Bonferroni correction (p < 0.05). RESULTS: There were no statistically significant differences among the cephalometric superimposition methods or when patients' sex was considered. CONCLUSION: Björk structural method, Steiner/Tweed SN line, Ricketts N-Ba line at N-point and Ricketts N-Ba line at CC-point methods were reliable and presented similar precision when the overall facial changes due to active growth and/or orthodontic treatment were examined.